Performance and Emission Analysis of Waste Cooking Oil Biodiesel Mixed with Titanium Oxide Nano-Additives - Raj Kumar; M. Arunkumar; D. Priestly Shan; Pravin P. Patil; Ravi Kumar; Bharat Singh; Velivela Lakshmikanth Chowdary (International Journal of Chemical Engineering)
People are using biodiesel in compression ignition engines because it is more environmentally friendly and can be used as a good alternative to diesel. There is a new technology called nanoparticles that can change the way a fuel works. Because waste cooking has a lot of oil in it, it can make biodiesel. To make biodiesel, transesterification was used to turn nonedible oil from waste cooking oil into biodiesel that could be used. Nanoparticles made of titanium oxide were studied by using scanning electron microscopy, transmission electron microscopy, as well as energy dispersive X-ray analysis, among other things. TiO2 nanoparticles are spread out in different amounts in the biodiesel blend. The dosage levels range from 25, 50, 75, and 100 ppm. Tests on how titanium nanoparticles in a waste cooking oil biodiesel blend affect a diesel engine’s performance and how it emits were conducted in this study too. At a steady speed, the engine was used when there was a lot of work to do. Tests show that the WCOME 20 TiO2 100 ppm blend worked well. With the increase in the concentration of nanoparticles, there is an increase in brake thermal efficiency and at the same time, there is a decrease in BSFC. It is also less harmful to the environment than other blends, except for NOx, which does no’t change.